Graduates' Perceptions of a Software Engineering Undergraduate Program: a view from postgraduation and industry - de Mello, Aline Vieira; Bordin, Andréa Sabedra; Finger, Alice Fonseca (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2020)
Software Engineering undergraduate programs began to emerge in Brazil in 1985. Nowadays there are about 75 courses in the country. Since then, software engineers have started attending postgraduate programs and working in the industry. The graduates’ perception is an important tool for the identification of positive and negative points related to different aspects of their education, as well as putting into practice improvements in the formation of the future graduates. In this context, the objective of this article is to analyse the perceptions of graduates of the Software Engineering undergraduate program at Unipampa about their graduation, considering the program's contribution to the postgraduate programs and the industry. A questionnaire with closed and open questions was sent to all graduates and the answers were analysed quantitatively and qualitatively. Based on the results, analyses were made and several contributions are presented, that may be useful to the academic community of software engineering education in the country, such as the adoption of active methodology Problem-Based Learning, the constant updating of the methodologies and technologies adopted by the undergraduate program, as well as continuous qualification of the professors.